Pengaruh Harga, Diskon dan Kualitas Produk terhadap Kepuasan Pelanggan Pada Bisnis Online Shop Lung.eraa di Surabaya - Prasetyo, Imam Bagus (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of price, discount, and product quality on customer satisfaction in the Lung.eraa online shop business in Surabaya. The research focuses on how these three variables affect customer satisfaction levels. Affordable prices encourage repeat purchases, while discounts play a significant role in increasing purchase intention. Additionally, good product quality is a key factor in creating customer satisfaction. This research employs a quantitative approach using a survey method by distributing questionnaires to 102 respondents who are Lung.eraa customers. Data were analyzed using multiple linear regression techniques to test the proposed hypotheses. The results indicate that price has a positive and significant effect on customer satisfaction, meaning that better pricing strategies lead to higher customer satisfaction. Discounts also show a positive and significant effect, demonstrating that attractive discount offers can enhance consumers' purchase intentions. This study contributes to the development of marketing strategies for online businesses by emphasizing the importance of managing price, discount, and product quality to improve customer satisfaction. Recommendations are provided for businesses to continuously improve these three aspects to maintain customer loyalty and expand market share in the e-commerce industry.